2012
DOI: 10.1128/ec.00155-12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Innovations within Oomycete Genomes: Insights into Biology, Pathology, and Evolution

Abstract: The eukaryotic microbes known as oomycetes are common inhabitants of terrestrial and aquatic environments and include saprophytes and pathogens. Lifestyles of the pathogens extend from biotrophy to necrotrophy, obligate to facultative pathogenesis, and narrow to broad host ranges on plants or animals. Sequencing of several pathogens has revealed striking variation in genome size and content, a plastic set of genes related to pathogenesis, and adaptations associated with obligate biotrophy. Features of genome e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 93 publications
(127 reference statements)
1
58
0
1
Order By: Relevance
“…These data show that the genes exhibited a transient expression pattern, where the mRNA transcripts were accumulated rapidly upon infection and might play an important role in the early stages of establishment of infection on taro. Oomycete pathogens rely on rapid metabolic processes during the early stages of infection for the production of infection related structures used to enter and feed from the host tissues and mRNA profiles exhibit dynamic changes during these developmental stages [24]. Our results were in agreement with the previous reports where the authors observed an early upregulation of pathogen genes during infection [18,19].…”
Section: Discussionsupporting
confidence: 94%
“…These data show that the genes exhibited a transient expression pattern, where the mRNA transcripts were accumulated rapidly upon infection and might play an important role in the early stages of establishment of infection on taro. Oomycete pathogens rely on rapid metabolic processes during the early stages of infection for the production of infection related structures used to enter and feed from the host tissues and mRNA profiles exhibit dynamic changes during these developmental stages [24]. Our results were in agreement with the previous reports where the authors observed an early upregulation of pathogen genes during infection [18,19].…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, haustorial oomycetes (Albugo laibachii, Hyaloperonospora arabidopsis, and Phytophthora spp.) also have lost the gene for thiamine biosynthesis (26).…”
Section: Resultsmentioning
confidence: 99%
“…These features suggest a functional converging evolution with phylogenetically unrelated biotrophic pathogens (20,26) and ectomycorrhizal symbionts (21,24). In contrast, the obligate biotrophic lifestyle of R. irregularis is not associated with a significant reduction in genes involved in nitrogen and sulfur assimilation, as observed in many obligate biotrophic leaf pathogens (20,26), but is associated with the high expression of genes involved in nutrient uptake (8). Thus, R. irregularis has the dual ability to interact with the soil environment with respect to mineral nutrient uptake and to integrate the complex cues imposed by its in planta life.…”
Section: Resultsmentioning
confidence: 99%
“…The sequenced oomycete pathogens genome size is from 37-Mb to 280-Mb and the predicted gene contents range from about 13,000 to 26,000 genes (Judelson 2012). The huge resources of the genome sequences provide more information for answering the questions about the biology, evolution, and pathogenesis of oomycete pathogens.…”
Section: Genomicsmentioning
confidence: 99%